Юридичні особи публічного права: постановка проблеми визначення критеріїв розмежування юридичних осіб публічного та приватного права - Олькіна, Олена Вікторівна; Олькина, Елена Владимировна; Ol'kina, Olena V. (My University, 2014)
Стаття присвячена проблемі визначення критеріїв розмежування юридичних осіб публічного та приватного права. Автор аналізує основні критерії виділення юридичних осіб публічного права, які були сформовані в юридичній доктрині та доходить висновку, що мета створення, а також інтерес, який покладено в основу діяльності юридичної особи є критерієм, що відображає сутність юридичної особи публічного права та зумовлює її правовий статус.

Статья посвящена проблеме определения критериев разграничения юридических лиц публичного права и юридических лиц частного права. Автор анализирует основные критерии выделения юридических лиц публичного права, которые были сформированы в юридической доктрине и приходит к выводу, что цель создания, интерес положенный в основу деятельности юридического лица является критерием, отображающим его сущность и определяющим его правовой статус.

The article deals with the criteria for differentiation legal entities of public and private law. The main criteria for identification the legal entities of public law in legal doctrine are justified as follows: the division of law into public and private law, which is the starting point for the division of legal entities into public and private; availability of public authority; integrity of the legal entity in public administration; the purpose of their activities; ownership, (they are based on a legal entity); method of formation (origin criterion) according to which legal entities of public law are created by the state, municipal bodies. The author claims that all of these criteria for identification of legal entities of public law disclose only some of their features, and do not characterize their nature due to the objective necessity of their functioning. Any legal entities are created for a specific purpose, for the implementation and protection of certain interests. Thus, the purpose and public interests that form the basis of legal entities of public law determine its legal status. Legal entities of private law are created to meet the interests of certain individuals and/or legal entities. Legal entities of public law are created to achieve the public interest, which is the basis of public law and public authorities.
Олькіна О. В. Юридичні особи публічного права: постановка проблеми визначення критеріїв розмежування юридичних осіб публічного та приватного права / О. В. Олькіна // Юридичний науковий електронний журнал. - 2014. - № 4. - С. 91-93. [Електронний ресурс]. - Режим доступу : http://www.lsej.org.ua/4_2014/23.pdf
Keywords: юридичні особи публічного права; публічний інтерес; публічна влада; юридичні особи приватного права; юридические лица публичного права; публичный интерес; публичная власть; юридические лица частного права; legal entities of public law; public interest; public authorities; legal persons of private law